IbM Pemanfaatan Limbah Jerami di Desa Banjarsari Kecamatan Sumberasih Kabupaten Probolinggo - Candra, Sulis Dyah; Sutrisno, Adi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
Most of the people in the village of Banjarsari, which is located in Sumberasih District at Probolinggo Regency,have the main livelihood as traditional farmers and ranchers. Rice straw is one of the agricultural byproducts that areavailable quite abundant in each planting season, and can be utilized as the basic ingredients of feed that can help theavailability of livestock nutrition supply in the dry season. Rice straw as the main ingredient of bokashi fertilizer, can alsobe used to increase the organic material content of paddy fields. One of the main causes the farmer and racher groupprefer to burn and not using this rice straw, is the process of choping the straw that takes up time and man hour. Thepurpose of the implementation of this event, is to raise awareness of farmers in order to increase yield productivity infarmers and farmers, since it would be easier for livestock to digest the straw and thus becoming more nutritious feed;also that the finely chopped straw will also improve the quality of composting in bokashi fertilizer processing. Themethods used to achieve these objectives are: Demonstration and Training, both theoretical and practical on the subjectof: (1) the engineering techniques of straw chopper machines; (2) procedure of straw chop machine maintenance andsafety; (3) usefulness and method of making straw-based feed; (4) usefulness and method of making bokashi fertilizermade from straw, (5) training farmer?s mindset of organization management, production and marketing good. The resultshows that most traditional farmers and ranchers never heard or understood about the usage of straw in for livestock feedand bokashi fertilizer, thus the technology and machine introduction were so welcomed in positive manner